A relação de causalidade no Direito Penal - Ronan de Oliveira Rocha (2014)
The present study critically examines the causality relationship in the ambit of Criminal Law. After define it and explicit its function in the theory of punishable act, it is broached the supposed crisis in which it would be immersed and investigated if there is, indeed, reason to put in check the causal paradigm as ontic and epistemic category. Then, the study conducts to the analysis of the interaction between causality and objective imputation, in order to know if the proposition of normative criterions in the sector of penal type makes it unnecessary to consider the causal nexus between conduct and result. Once delimited the boundaries of causality, the main theories of causation in criminal law are broached, with emphasis on the conditio sine qua non’s theory, adopted in the Brazilian Penal Code. Its deficiencies are pointed out as well the answers of its defenders and the current state of discussion about the topic. Afterwards, the controversy of causality in the improper omissive crimes is broached and different proposals of constitution of the objective type of those crimes are analyzed, in order to clarify which criterions must be examined by the judge at the time of application of criminal law. Finally, the cases initially proposed are solved with the application of the adopted theory.